2018
DOI: 10.1038/s41598-018-22361-2
|View full text |Cite
|
Sign up to set email alerts
|

Three dimensional electron microscopy reveals changing axonal and myelin morphology along normal and partially injured optic nerves

Abstract: Following injury to the central nervous system, axons and myelin distinct from the initial injury site undergo changes associated with compromised function. Quantifying such changes is important to understanding the pathophysiology of neurotrauma; however, most studies to date used 2 dimensional (D) electron microscopy to analyse single sections, thereby failing to capture changes along individual axons. We used serial block face scanning electron microscopy (SBF SEM) to undertake 3D reconstruction of axons an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 70 publications
2
33
0
Order By: Relevance
“…Axon diameter along with myelin thickness [154], internode [155] and paranode gap [156] determines the functional properties of the nerves [157]. Axon diameter has been used to determine conduction velocity along various pathways.…”
Section: The Retrolaminar Regionmentioning
confidence: 99%
“…Axon diameter along with myelin thickness [154], internode [155] and paranode gap [156] determines the functional properties of the nerves [157]. Axon diameter has been used to determine conduction velocity along various pathways.…”
Section: The Retrolaminar Regionmentioning
confidence: 99%
“…Many studies have used this model [4][5][6][7][8][9][10][11][12][13] . In these previous studies, PONT in rats was administrated from the superior side of optic nerves; however, in this study we cut the optic nerves from the temporal side and found that this operation was much easier to conduct than from the superior side due to the lack of obstruction from rectus superior and obliquus superior eye muscles ( Fig.…”
Section: Glaucoma and Partial Optic Nerve Transection Modelmentioning
confidence: 99%
“…The diameter of the long and thin axon has long been believed to be uniform for the same type of neurons. However, with the development of 3D EM reconstruction, diameter fluctuations have been detected along the length of axons in optical nerves (Giacci et al, 2018). Similarly, in live rat brains, axonal diameter fluctuations were revealed with super-resolution microscopy after the conduction of action potentials (Chereau et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the expansion of axonal diameter surrounding large cargoes, i.e. autophagosomes 8 or mitochondria 9 , has been observed by super-resolution microscopy and 2D-electron microscopy (EM) in both normal and degenerating axons 10, 11 . Considering the spatial limitation exerted by the rigid axon membrane 12 , the trafficking of large cargoes is likely to be affected.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation